Motivasi Belajar Mahasiswa Keperawatan Kritis Menggunakan Metode Pembelajaran Kooperatif Tipe Think-Pair-Square (TPS): Student Motivation to Learn Critical Nursing Using Think-Pair-Square (TPS) Type of Cooperative Learning - Asdiwinata, I Nyoman; Yundari, AA Istri Dalem Hana; Saraswati, Ni Luh Gede Intan (Bali Medika Jurnal, 2021)
Background: The learning activities carried out by students so far only rely more on lecture subjects. This is felt to be less challenging and enthusiastic in carrying out the learning process. This is evident from the decline in student interest in attending every lecture that is carried out. Of course, motivation in learning will be greatly influenced by many factors, internal or external. The application of certain learning models is expected to be able to help students achieve learning targets. It is expected that the thinik-pair-square type of cooperative learning model can increase student learning motivation. Purpose: The purpose of this study was to explore the effectiveness of the think-pair-square (TPS) cooperative learning model on critical nursing learning motivation. Methods: This study used a research design with one group pretest-posttest technique. data collection using purposive sampling. The questionnaire was tested using the Rasch Model to see its reliability and validity and the logit result was 0.89. Results: The results of this study indicate that the majority of respondents are women as much as 85%. Based on the results of different tests using the Wilcoxon Signed Rank Test in the treatment group, the significance value was less than 0.05 which proved that there were differences in motivation before and after being given treatment. Conclusion: Changes in the motivation value of students after being given a different type of think-pair-square learning indicate that this method was successful for students in conducting critical nursing learning.